Multiple Patterns of Axonal Collateralization of Single Layer III Neurons of the Rat Presubiculum - Honda, Yoshiko; Furuta, Takahiro (Frontiers in Neural Circuits, 2019)
The presubiculum plays a key role in processing and integrating spatial and head-directional information. Layer III neurons of the presubiculum provide strong projections to the superficial layers of the medial entorhinal cortex in the rat. Our previous study revealed that the terminal distribution of efferents from layer III cells of the presubiculum was organized in a band-like fashion within the medial entorhinal cortex, and the transverse axis of these zones ran parallel to the rhinal fissure. Identifying axonal branching patterns of layer III neurons of the presubiculum is important to further elucidate the functional roles of the presubiculum. In the present study, we visualized all axonal processes and terminal distributions of single presubicular layer III neurons in the rat, using in vivo injection of a viral vector expressing membrane-targeted palmitoylation site-attached green fluorescent protein. We found that layer III of the rat presubiculum comprised multiple types of neurons (n=12) with characteristic patterns of axonal collateralization, including cortical projection neurons (n=6) and several types of intrinsic connectional neurons (n=6). Two of six cortical projection neurons provided two or three major axonal branches to the medial entorhinal cortex and formed elaborate terminal arbors within the superficial layers of the medial entorhinal cortex. The width and axis of the area of their terminal distribution resembled that of the band-like terminal field seen in our massive-scale observation. Two of the other four cortical projection neurons gave off axonal branches to the medial entorhinal cortex and also to the subiculum, and each of the other two neurons sent axons to the subiculum or parasubiculum. Patterns of axonal arborization of six intrinsic connectional neurons were distinct from each other, with four neurons sending many axonal branches to both superficial and deep layers of the presubiculum and the other two neurons showing sparse axonal branches with terminations confined to layers III-V of the presubiculum. These data demonstrate that layer III of the rat presubiculum consists of multiple types of cortical projection neurons and interneurons, and also suggest that inputs from a single presubicular layer III neuron can directly affect a band-like zone of the medial entorhinal cortex.